The value of mentorship in medical education. (4th February 2016) - Dalgaty, Faith; Guthrie, Greg; Walker, Heather; Stirling, Kevin
Summary: Background: The transition from senior medical student to working safely and effectively as a new junior doctor is one of the biggest challenges that a new graduate will face. In 2014 the General Medical Council published The state of medical education and practice in the UK, reporting that some new doctors continue to struggle with increased responsibilities. We classify these instances as a 'performance gap', describing occasions in clinical practice where an individual exceeds their performance capacity. The Medical Mentorship Programme addressed identified performance gaps through a structured curriculum of simulation‐based education and facilitated clinical practice. Methods: Programme content was based on the experiences of the authors and their peers in graduating from their undergraduate training programme and becoming junior doctors. A questionnaire was disseminated to junior doctors in their first clinical rotation. The questionnaire asked doctors to describe instances where they experienced a performance gap. These data informed the development of the Medical Mentorship Programme. The effect of this programme was then evaluated via focus group discussion. Results: The Medical Mentorship Programme has been shown to be an effective conduit for supporting the transfer of learning needed to address performance gaps in students. The programme increased the confidence of students in preparation for clinical practice and allowed junior doctors to reflect on their professional development. The programme combined complementary teaching techniques – mentorship, simulation and direct clinical experience – to aid the professional development of both students and mentors. Some new doctors continue to struggle with increased responsibilities